Subacute but not acute generation of nitric oxide in focal cerebral ischemia - Faßbender, Klaus; Fatar, Marc; Ragoschke-Schumm, Andreas; Picard, Martin; Bertsch, Thomas; Kühl, Sandra; Hennerici, Michael G. (Stroke, 2000)
BACKGROUND AND PURPOSE: Excessive release of nitric oxide (NO) has been implicated in the pathophysiology of neurodegeneration in ischemic stroke. We compared intracerebral release of indicators of NO generation at the acute and subacute stages of transient focal cerebral ischemia. - METHODS: In vivo microdialysis in the rat striatum was performed at the acute (first hours) and subacute (after 24 or 48 hours) stages of cerebral ischemia or sham operation to monitor intracerebral release of the stable NO metabolites nitrite and nitrate. - RESULTS: Whereas only a nonsignificant trend toward increased release of these NO metabolites was evidenced in acute cerebral ischemia, a significant NO generation was observed subacutely, 48 hours after induction of cerebral ischemia. Aminoguanidine, a selective inhibitor of inducible NO synthase, suppressed this delayed release of nitrite and nitrate. - CONCLUSIONS: Whereas these observations do not support a major NO generation in acute cerebral ischemia, they indicate an inducible NO synthase-dependent NO generation predominantly at the subacute phase of ischemic neurodegeneration. Therefore, NO generation may play a pathophysiological role in delayed ischemic neurodegeneration.
Gesehen am 19.07.2022